PENGARUH JUMLAH WISATAWAN DAN TINGKAT HUNIAN KAMAR HOTEL TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KOTA MATARAM TAHUN 2015 – 2020 - Abdul Rahman; Rosita Rosita (Nusantara Hasana Berdikari, 2022)
This study aims to measure the significance of the partial influence of the influence of the number of tourists and hotel room occupancy rates on local revenue in Mataram City in 2015 – 2020; and to measure the simultaneous significance of the influence of the number of tourists and hotel room occupancy rates on local revenue in Mataram City in 2015 – 2020); and to measure the dominance of the number of tourists and hotel room occupancy variables on local revenue in Mataram City in 2015 – 2020. The research was conducted in Mataram City and the type of research used in this study is quantitative research with an associative approach. While the data used in this study is secondary data. The results showed that: 1) the number of tourists and hotel room occupancy rates had a significant partial effect on local revenue (PAD) in the city of Mataram; 2) The number of tourists and hotel room occupancy rates have a significant simultaneous effect on local revenue (PAD) in the city of Mataram; 3) The number of tourists has a more dominant influence on local revenue (PAD) in the city of Mataram in 2015 – 2020.